The Effect of Implementing an Electronic Medical Record (EMR) System on Patient Data Management at the Outpatient Clinic of Rumkit Tk. IV 01.07.02 Binjai in 2025 - Anna Ivra Soleliza Jones; Felix Kasim; Tati Murni Karokaro (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
The Electronic Medical Record (EMR) system is a crucial component in improving the quality of healthcare services through fast, accurate, and integrated patient data recording. The Outpatient Clinic of Rumkit Tk. IV 01.07.02 Binjai has fully implemented the EMR system; however, its implementation still faces several challenges, including limited computer devices, network disruptions, unstable electricity, and variations in users’ ability to operate the system, which may affect the effectiveness of patient data management. This study aims to analyze the effect of EMR implementation on patient data management, including time efficiency, data accuracy, cost savings, and healthcare workers’ satisfaction. This research employed a quantitative approach with a descriptive-analytic design, involving a sample of 38 healthcare workers representing the total population of EMR users. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability, supported by observation. Data analysis was conducted using univariate analysis, bivariate analysis with the chi-square test, and multivariate analysis using multiple linear regression. The results showed that EMR implementation was significantly associated with time efficiency, data accuracy, cost savings, and healthcare workers’ satisfaction (p < 0.05). Regression analysis indicated that data accuracy and time efficiency were the most dominant variables contributing to improved patient data management. It can be concluded that the implementation of the EMR system has a significant effect on patient data management at the Outpatient Clinic of Rumkit Tk. IV 01.07.02 Binjai. Therefore, improvements in technological infrastructure, routine training, and handling of technical obstacles are needed to optimize EMR utilization and maximize its impact on healthcare service quality.